Deconstructing the Queen Bee Syndrome: Social Identity Theory and Female Leadership in Organizational Contexts - Chuco Aguilar, Victoria Judith (2024)
Introduction: The Queen Bee Syndrome, a phenomenon in which women in leadership positions inhibit the advancement of other women, poses a significant challenge in the pursuit of gender equality in the workplace. Aim: This study aims to explore the Queen Bee Syndrome within the framework of social identity theory in the context of organizational behavior. Methods: A comprehensive literature search was conducted using key terms such as "Queen Bee Syndrome", "gender inequality", "social identity theory" and "organizational behavior" in several databases. Results: The review identifies that the Queen Bee Syndrome exacerbates gender disparities and contributes to a toxic work environment by reinforcing gender bias and hindering women's career advancement. The roots of the syndrome are often found in the internalization of masculinized leadership attributes and societal biases that favor male dominance. Conclusions: Addressing the Queen Bee Syndrome requires a multifaceted approach, including ensuring balanced representation of men and women, promoting positive role models, and incorporating equality principles into organizational policies to foster a more inclusive and women-friendly environment.